The Influence of the Effectiveness of Supervision and the Government Internal Control System (SPIP) on the Performance Assessment of Local Government at the Regional Inspectorate of Nunukan Regency - Musdalifah; Muliyadi Hamid; St. Rukaiyah (Economos : Jurnal Ekonomi dan Bisnis, 2025)
The performance assessment of local government is a crucial part of achieving accountable and effective governance. This study aims to analyze the influence of supervision effectiveness and the Government Internal Control System (SPIP) on performance assessment by the Regional Inspectorate of Nunukan Regency. The research method used is a quantitative approach with multiple linear regression analysis techniques. Data were collected through questionnaires distributed to 44 respondents who are personnel within the Regional Inspectorate. The results show that the effectiveness of supervision has a significant influence on performance assessment, as indicated by a significance value of 0.000 and a positive regression coefficient. This suggests that timely, comprehensive, and well-followed-up supervision can improve the quality of performance assessments of local government units. Additionally, SPIP also has a significant influence on performance assessment, with a significance value of 0.002 and a positive coefficient. The implementation of SPIP covering control environment, risk assessment, control activities, communication, and monitoring has been proven to support the achievement of local government performance indicators. Simultaneously, the two independent variables contribute 78.9% to the performance assessment. These findings highlight the importance of strengthening supervision and internal control systems in supporting the optimal performance of local governance.